ANALISIS PENGARUH INOVASI PRODUK DAN KEWIRAUSAHAAN TERHADAP STRATEGI PEMASARAN DALAM MEMBANGUN KINERJA PEMASARAN (Studi pada Pengrajin Kayu Jati di Blora) - Kumalasari, Elviana Niken; Sugiarto, Yohanes (Faculty of Economics and Business Diponegoro University, 2016)
Micro, Small and Medium Enterprises (MSME) can help cultivate existing resources in each area. This has contributed greatly to local income and revenue of Indonesia, such as the small and medium industries in the city Blora. Blora is one of the districts that are in the province of Central Java, which has many MSME in the centers - centers of industry, one of the industrial centers that the public interest Blora is teak wood processing industry or the furniture. This study aimed to investigate the effect of the product innovation and entrepreneurial marketing strategy to build marketing performance. The total sample of 82 respondents teak wood craft entrepreneurs in Blora. Data were obtained from questions by using a questionnaire consisting of closed and open questions. Respondents were analyzed with two-stage regression analysis tools SPSS (Statistical Package for Social Science). Based on the analysis conducted shows that product innovation positive and significant impact on the performance of marketing, product innovation positive and significant impact on marketing strategies, entrepreneurial positive and significant impact on marketing strategies, entrepreneurial positive and significant impact on the performance of marketing, but marketing strategy had no significant effect the performance of marketing.